The Influence of Principal Leadership and Communication on Educator Performance in Elementary Schools in the Catur Cluster Single - Nurtilawati Nurtilawati; Alhadi Yan Putra; Rohana Rohana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of principal leadership and communication on the performance of educators in Public Elementary Schools in the Catur Tunggal Cluster. Educator performance is greatly influenced by various factors, including effective principal leadership and good communication. This study uses a quantitative approach with a survey method involving 50 educators in elementary schools that are members of the cluster. Data were collected through questionnaires distributed to respondents, which were then analyzed using multiple linear regression analysis. The results of the study indicate that there is a positive and significant influence between principal leadership and communication on educator performance. Principals who are able to demonstrate good leadership and establish effective communication with educators will improve their performance. This study is expected to contribute to the development of educational management at the elementary school level.